Vocal Fatigue Assessment in Female Islamic Scholars - Gupta, Ayush; Gupta, Girik (Journal of Educational Research and Policies, 2025)
Alimiah are female Islamic scholars who are regarded as professional voice users since they utilize their voices on a regular basis to impart knowledge. The S/Z ratio is a vocal function indicator that aids in determining whether voice issues occur. Thirty Alimiah were enrolled in the current study, which evaluates the s/z ratio among them. The results of the current study, which comprised 30 Alimiah, indicated that the majority of them had higher than usual s/z ratios, which suggests that they are at risk of having voice issues.